STYLISTIC VARIATIONS IN TRANSLATED TEXTS (IN THE EXAMPLE OF "THE UNBEARABLE LIGHTNESS OF BEING" BY MILAN KUNDERA) (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the stylistic variations found in the translated versions of Milan Kundera’s The Unbearable Lightness of Being. It examines how different translators, such as Michael Henry Heim and Peter Kussi, navigate the challenges of conveying Kundera’s complex prose and philosophical reflections. The article highlights how the stylistic choices made in translation—ranging from linguistic accuracy to creative adaptations—affect the reader’s experience of the text. By focusing on the shifts in tone, narrative structure, and cultural context, the article underscores the importance of stylistic fidelity in literary translation. It also discusses how these variations contribute to the novel’s interpretation and accessibility across different languages and cultures, revealing the dynamic role of translation in shaping global literary reception.